Organic mulch can increase the survival of a weed biological control agent during laboratory mass rearing. Issue 9 (2nd September 2019) - Halbritter, Dale A.; Wheeler, Gregory S.
ABSTRACT: Mass rearing agent organisms is a critical component to classical biological control programmes. Maximising survival of each life stage necessitates that ideal, stage-specific conditions are available in the rearing protocol. We investigated a method to improve pupal survival of Pseudophilothrips ichini Hood (Thysanoptera: Phlaeothripidae), a proposed biological control agent of the highly invasive Brazilian peppertree, Schinus terebinthifolia Raddi (Sapindales: Anacardiaceae). Specifically, we tested the effect of organic mulch on the number of adults emerging. Either compressed coconut fibre, dried Brazilian peppertree leaves, or dried sphagnum moss were added to the soil surface of potted Brazilian peppertrees. Nothing was added to untreated control plants. Each plant was sealed in a clear acrylic cylinder and 50 s instar thrips were added. The number of adults emerging was compared between mulch treatments. The greatest number of adults emerged from plants with sphagnum moss, with no differences among the other mulches and the control. We confirmed that the majority of thrips pupated in the moss rather than in the soil. Relative humidity was higher in the mulch layers compared to the plant canopy. Sphagnum moss likely provided the most ideal harbourages for thigmotactic pupae and the humid microhabitat minimised desiccation. We discuss the use of organic mulches in ecological contexts and emphasise the benefits of organic mulch in captive rearing operations that involve insects with soil-dwelling stages.